Pengaruh Strategi Pemasaran Online Terhadap Keputusan Pembelian Konsumen - Hotman Nicolas Badjo; Muhammad Zayyid Mubarok; Rivaldi Muhamad Fitroh; Septian Kharist; Ridho Rafliansyah; Riski Saputra; Eva Zuraidah (TIN: Terapan Informatika Nusantara, 2023)
Noys Vapehouse is a vapestore that has just opened in East Jakarta, more precisely in July 2023. Noys Vapehouse sells various kinds of vape tools and equipment and sells the latest products. Not only that, but there are other things that attract consumers to make purchasing decisions at Noys Vapehouse using quantitative methodology. In collecting this data, the following data collection methods were used: 1. making direct observations and observations regarding matters related to the influence of online marketing strategies on consumer purchasing decisions. 2. Literature study The aim of this research is to study and analyze how online marketing strategies influence purchasing decisions made by consumers. It was concluded that of the 56 respondents used as a sample each had data of 4 people (7%) aged 13-17, 47 people (84%) aged 18-25, 3 people (5%) aged 26-39, and 2 people (4%) aged 40-49, it was concluded that of the 56 respondents sampled, 37 people (66%) were male and 19 people (34%) were female. The influence of online marketing strategies on consumer purchasing decisions is very significant. By leveraging online platforms, companies can reach consumers more effectively, provide more accessible information, and create greater engagement. Providing informative content and online promotions can influence consumer perceptions of products, thus, online marketing strategies are key in gaining consumer support and increasing sales.